OVERVIEW OF FAMILY SUPPORT AND KNOWLEDGE ABOUT THE DASH DIET IN HYPERTENSIVE PATIENTS - Vita Dwi Septiningsih; Agik Priyo Nusantoro; Siti Nurjanah (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Prolonged hypertension can slowly damage blood vessels and trigger heart attacks, strokes, and kidney failure. The American Heart Association recommends managing hypertension with the Dietary Approaches to Stop Hypertension (DASH) diet. Family support affects DASH diet adherence through four mechanisms: instrumental, informational, rewarding, and emotional. The study aimed to assess the level of family support and understanding of the DASH diet among hypertensive patients in Flamboyant Ward 8 at Dr. Moewardi Hospital.Methods: This study employed a quantitative observational design with a descriptive cross-sectional approach. The population of this study is the family of hypertension patients in the Flamboyant Ward 8 of Dr. Moewardi Hospital, with a sample size of 82 respondents, using accidental sampling. Data were collected using questionnaires. Results: The results of this study showed that the characteristics of the majority of respondents aged 36-45 years (late adults) amounted to 34 respondents (41.5%), female sex amounted to 45 respondents (54.9%), and SMK/SMA education level amounted to 32 respondents (39.0%). The level of family support for the majority of the good category was 46 respondents (56.1%), and the level of knowledge about the DASH diet among the majority of the good category was 37 respondents (45.1%).Conclusion: This study indicates that most families of hypertensive patients demonstrated strong family support, while knowledge of the DASH diet was comparatively low. These findings highlight the need to strengthen informational and educational interventions to complement existing family support and optimize non-pharmacological hypertension management.